High Mitochondrial DNA Copy Number Is a Protective Factor From Vision Loss in Heteroplasmic Leber's Hereditary Optic Neuropathy (LHON) - Bianco, Angelica; Bisceglia, Luigi; Russo, Luciana; Palese, Luigi L.; D'Agruma, Leonardo; Emperador, Sonia; Montoya, Julio; Guerriero, Silvana; Petruzzella, Vittoria (Investigative ophthalmology & visual science, 2017)
Leber's hereditary optic neuropathy (LHON) is a mitochondrial disease that typically causes bilateral blindness in young men. It is characterized by as yet undisclosed genetic and environmental factors affecting the incomplete penetrance. We identified 27 LHON subjects who possess heteroplasmic primary LHON mutations. Mitochondrial DNA (mtDNA) copy number was evaluated. The presence of centrocecal scotoma, an edematous, hyperemic optic nerve head, and vascular tortuosity, as well as telangiectasia was recognized in affected subjects. We found higher cellular mtDNA content in peripheral blood cells of unaffected heteroplasmic mutation carriers with respect to the affected. The increase of cellular mtDNA content prevents complete loss of vision despite the presence of a heteroplasmic state of LHON primary mutation, suggesting that it is a key factor responsible for penetrance of LHON.